The versatility of buccal pad of fat as an adjunct flap in cleft palate repair (Indian Journal of Case Reports, 2020)
The buccal pad of fat (BFP) has a variety of applications in cleft palate surgery. Early dehiscence and fistula formation in the cleft palate repair are common complications encountered due to closure under tension, poor handling of tissues, and failure to achieve a layered closure. This case series emphasizes the use of a bilateral pedicled BFP graft as a separate layer in wide primary cleft palate repair when the nasal mucosal layer is sutured under tension and also in a case of nasal mucosal tear while suturing to avoid palatal fistulas postoperatively. No recurrence was seen and the donor site healed well without esthetic or significant functional impairment. The post-operative course was uneventful. This series confirms the excellent and predictable healing of BFP intraorally and the minimal morbidity associated with the use of such grafts in cleft palate surgeries.